القطاع المحفوظ لقلعة بني راشد - بن عيسى, احمد (University of Eloued جامعة الوادي, 2023)
يتناول هذا المقال التعريف بالقطاع المحفوظ لقلعة بن راشد حيث تعتد من المدن الحضارية التي تعاقبت عليها العديد من الفترات التاريخية، مخلفة نسيج عمراني ذو طابع إسلامي يتميز بالبساطة في التركيبة المعمارية والحصانة الطبيعية بحكم موقعه وحدوده الجغرافية، كما ساهمت قلعة بني راشد في ازدهار الحركة العلمية والثقافية بشكل كبير بفضل زواياها ومساجدها. وعليه سنحاول من خلال هذه الورقة العلمية إبراز جميع هذه القيم التي تتطلب اقتراح إنشائها ضمن قائمة القطاعات المحفوظة من أجل حمايتها وتثمينها. This article deals with the definition of the preserved sector of the Qalaa of Beni-Rached which considered as one of the civilised cities that have successively many historical periods leaving an urban fabric of an Islamic character marked by simplicity in the architectural composition and natural immunity because of Its location and geographical boundaries. The Qalaa of Beni Rached contributed greatly as well in the flourishing of the scientific and cultural movement thanks to Its Quranic schools and mosques and through this we will try from this scientific paper showing all the values that the city of Qalaa bounds that push to Its contruction within the list of the preserved sctors to protect and value it. contruction with in the list of the preserved sctors to protect and valne it.